Oblique incidence investigations of the ionosphere over the Southern Ocean - Rash, Jonathan Paul Stuart (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1979)
The region of the South Atlantic and Southern Oceans ... is of considerable interest in ionospheric and aeronomic research owing to the presence of several 'anomalies'. The most notable of these is the South Atlantic (or Brazilian) Anomaly associated with the global minimum of magnetic field intensity off the coast of Brazil (Introduction, p. 1)
Keywords: Ionosphere; Ionosphere -- Antartctic Ocean